Neuroprotective effect of S-allyl cysteine on an experimental model of multiple sclerosis: Antioxidant effects. (March 2018) - Escribano, B.M.; Agüera, E.; Aguilar-Luque, M.; Luque, E.; Feijóo, M.; LaTorre, M.; Giraldo, A.I.; Galván-Jurado, A.; Caballero-Villarraso, J.; García-Maceira, F.I.; Santamaría, A.; Túnez, I.
Highlights: Experimental autoimmune encephalomyelitis consistently induces motor impairment. S-allyl cysteine (SAC) improves motor impairment in this model. SAC attenuates oxidative stress in the central nervous system. SAC decreases cell damage in brain. Abstract: S-allyl cysteine (SAC), has shown itself to performance important activity as a neuroprotective agent. This action is prompted by antioxidative activity. The aim of this study was to evaluate the neuroprotective effect of SAC, the principal organosulfur compound of garlic, on experimental autoimmune encephalomyelitis (EAE) as a model of multiple sclerosis (MS). Young-adult Dark Agouti rats were used. The experimental model of EAE was carried out by means of mielyn oligodendrocyte glycoprotein (MOG). The effects of MOG were evaluated by changes in: clinical score, biomarkers of oxidative/nitrosative stress, antioxidants, mitochondrial viability and neurohistologic viability. Our results reveal that MOG causes oxidative/nitrosative damage in brain and spinal cord, a decrease in the glutathione redox system and cell loss, whereas SAC administration attenuates the effects of MOG. In addition, SAC was the most effective treatment used in this study. The data show the ability of SAC to modify the development of EAE.